2020
DOI: 10.1088/1757-899x/788/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

The potential of wind velocity in the Banda Aceh coast to the ability to generate electrical energy by horizontal axis wind turbines

Abstract: The wind is air that moves from a high-pressure area to a low-pressure area. Indonesia has the potential of winds that have speeds ranging from 2 m/s to 6 m/s which blow for a period of 6 hours/day. Many researchers have examined what kinds of problems are in the context of wind turbine energy generation. This study discusses the effect of wind speed and variations in the number of turbine blades on the power generated by horizontal wind turbines to rotate generators, case studies on the coast of Banda Aceh. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Studies that are carried out to optimize the design of wind turbines often lead not to a simplification of the design of the wind turbine but on the contrary, to its complication. In work [26], an installation with an auxiliary wind wheel, which is located on the same axis of rotation with the main wind wheel, is considered. The auxiliary wind wheel has 8-12 blades and is used in a complete set of five types of models of double wind turbines.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Studies that are carried out to optimize the design of wind turbines often lead not to a simplification of the design of the wind turbine but on the contrary, to its complication. In work [26], an installation with an auxiliary wind wheel, which is located on the same axis of rotation with the main wind wheel, is considered. The auxiliary wind wheel has 8-12 blades and is used in a complete set of five types of models of double wind turbines.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The Data has collected to measure the wind speed, the generator shaft's rotational speed, and the resulting electric current. The results showed that wind speeds below 5 m / s are ideal for using three blades and wind speeds of more than 7 m / s are better for using blades of more than 3 [1].…”
Section: Introductionmentioning
confidence: 99%